HIV prevalence and impact on renutrition in children hospitalised for severe malnutrition in Niger: an argument for more systematic screening. - Yoann Madec (Public Library of Science (PLoS), 2011)
Background In developing countries, malnutrition is a contributing factor in over 50% of child deaths. Mortality rates are higher in underweight children, and HIV-infection is known to increase underweight. Our goals were to evaluate the prevalence of HIV among children hospitalised for severe malnutrition (SM) at the Niamey national hospital (Niger), and to compare renutrition and mortality by HIV-status. Methods Retrospective study based on all children <5 years hospitalised for SM between January 1(st) 2008 and July 1(st) 2009. HIV-prevalence was the ratio of HIV+ children on the number of children tested. Duration of renutrition and mortality were described using survival curves. Results During the study period, 477 children were hospitalised for SM. HIV testing was accepted in 470 (98.5%), of which 40 were HIV+ (HIV prevalence (95% confidence interval) of 8.6% (6.2-11.5)). Duration of renutrition was longer in HIV+ than HIV- children (mean: 22 vs. 15 days; p = 0.003). During renutrition, 8 (20%) and 61 (14%) HIV+ and HIV- children died, respectively (p = 0.81). Conclusion Around 9% of children hospitalised for severe malnutrition were HIV infected, while in Niger HIV prevalence in adults is estimated at 0.8%. This pleads for wider access to HIV testing in this population.